Backward disequilibrium in elderly subjects - Manckoundia, Patrick; Mourey, France; Pérennou, Dominic; Pfitzenmeyer, Pierre (Clinical interventions in aging, 2008)
Backward disequilibrium is observed frequently in daily clinical practice. However, there are no epidemiological data concerning this postural disorder. Defined by a posterior position of the centre of mass with respect to the base of support, backward disequilibrium is abnormal postural behavior, usually characterized by a posterior trunk tilt in standing and sitting positions, which predisposes subjects to backward falls. Many afflictions whether they are somatic (degenerative, ischemic and traumatic brain lesions), psychosomatic (psychomotor disadaptation syndrome, confinement to bed, nonuse situations) or psychological (depression) can cause backward disequilibrium. A vicious circle of falls, and loss of autonomy can arise and this is the main consequence of backward disequilibrium. Thus, in this paper, we review backward disequilibrium in elderly subjects with regard to the causes, consequences, assessment, and management.